Research for the social improvement and general betterment of Lydia Goldblatt & Julie Graham-Chang - Ignatow, Amy (New York : Amulet Books, 2011)
Two best friends embark on a project to study the behavior and taste of the popular girls at their elementary school so that by the time they get to middle school they too will be in the right crowd and record their findings in the form of a scrapbook.
Keywords: Scrapbooks -- Juvenile fiction; School fiction